Implementation Of Social Studies In Elementary Schools In The National Curriculum In Private Schools - Panni Adibah Harahap; Otong Djuharie; Andang Saehu (Lembaga Pengembangan Kinerja Dosen, 2025)
This study discusses social media-based English learning strategies in a case study on @glishbygiovana Instagram account. The background of the study is based on the increasing use of social media as a flexible alternative learning tool, especially among the younger generation. The main objective of this study is to analyze the type of content, presentation format, audience interaction, and the impact of reporting English skills on increasing followers. The study utilized a descriptive qualitative method in a case study approach. The results showed that short videos such as stories and comments, educational signatures, and interactive characteristics successfully attracted users' attention and increased active participation in the learning process. The interaction formed between accounting assistants and followers creates a supportive and dynamic learning community. These results suggest that social media, particularly Instagram, can be an effective and enjoyable learning tool when consistently relevant. The effectiveness of this study demonstrates the potential of social media as an adaptive educational platform for modern learning needs and can be used as a model for formal non-classroom English teaching strategies.